Biofilm-based Healthcare-associated Infections Volume II - Donelli, Gianfranco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The aim of this book is to provide readers with a wide overview of the main healthcare-associated infections caused by bacteria and fungi able to grow as biofilm. The recently acquired knowledge on the pivotal role played by biofilm-growing microorganisms in healthcare-related infections has given a new dynamic to detection, prevention and treatment of these infections in patients admitted to both acute care hospitals and long-term care facilities. Clinicians, hygienists and microbiologists will be updated by leading scientists on the state-of-art of biofilm-based infections and on the most innovative strategies for prevention and treatment of these infections, often caused by emerging multidrug-resistant biofilm-growing microorganisms.
Persister cells in biofilm associated infections -- Fungal biofilms in human disease -- Biofilm-Infected Pressure Ulcers: Current Knowledge and Emerging Treatment Strategies -- Microbial biofilms and adverse reactions to gel fillers used in cosmetic surgery -- Role of biofilms in breast implant associated infections and capsular contracture -- Innovative strategies for combating biofilm-based infections -- Antimicrobial polymers for anti-biofilm medical devices: state of art and perspectives -- Antimicrobial Photodynamic Therapy for Treatment of Biofilm-based Infections -- Anti-Biofilm Agents in Control of Device-Related Infections -- Lipid- and polymer-based drug delivery carriers for eradicating microbial biofilms causing medical device-related infections.
Keywords: Medical microbiology; Bacteriology; Infectious diseases; Medical Microbiology; Bacteriology; Infectious Diseases